Рrevention and rehabilitation of health problems of schoolchildren from the zone of military conflict in Ukraine - I.S. Lebets; V.O. Dynnik; T.M. Matkovskaya; N.V. Medvedovska; D.A. Kashkalda (Medičnì Perspektivi, 2022)
The purpose of the research is to justify the necessity for rehabilitative medical and psychological support of schoolchildren from the zone of military conflict with psychosomatic disorders, psychological divergences in conditions of post-traumatic stress of different levels. There were surveyed 286 children of school age who suffered as a result of military conflict in the East of Ukraine. Anxiety, the level of stress, psychological, emotional internal health, the intensity of stress-realizing systems (cortisol, adrenaline, norepinephrine, diene conjugates, thiobarbituric acid-active products) and stress-limits of systems (serotonin, methlorinate, recovered glutathione, glutathionoperoxidase, superoxide-midase) were assessed. It is established that in the majority (59.52%) of schoolchildren from the Joint Forces Operation (JFO) zone in both boys and girls an increased level of emotional tension was recorded. It was found that the past stress provokes the activation of stress-regulating systems, the severity of which depends on the intensity of stress. Cortisol, diene conjugates, thiobarbituric acid-active products, reduced glutathione, melatonin play a special role in these processes. Children-migrants have a higher level of certain indices of the stress-realizing system (adrenaline) compared to schoolchildren from the military zone, which confirms the influence of a place of living as an additional stress factor on the child's body. It was found that most of the surveyed children have numerous somatic and psychosomatic complaints, and clinical symptoms are characterized by polymorphism. Among organic and functional disorders, diseases of the digestive, endocrine system, neurotic and non-psychotic disorders of residual-organic genesis dominate. The problem of deteriorating health status of schoolchildren from the zone of military conflict was revealed, a possibility of systematic impact on preservation and strengthening the health of this contingent was justified. The revealed disorders of the psychosomatic health of children from the zone of military conflict require a multidisciplinary approach (consulting and follow-up of specialist-doctors of various profiles) to prevent their progression.